Joint Effect of Multiple Prothrombotic Genotypes and Mean Platelet Volume on the Risk of Incident Venous Thromboembolism - Jakobsen, Lisa; Frischmuth, Tobias; Brækkan, Sigrid K.; Hansen, John-Bjarne; Morelli, Vânia M. (Thrombosis and Haemostasis, 2022)
Background A high mean platelet volume (MPV), a marker of increased platelet reactivity, is a risk factor for venous thromboembolism (VTE). Whether established prothrombotic single nucleotide polymorphisms (SNPs) further increase the VTE risk in subjects with high MPV because of biological interaction remains unknown.Aim To investigate the joint effect of high MPV and prothrombotic genotypes, comprising a 5-SNP genetic risk score (GRS), on the risk of VTE in a population-based case–cohort.Methods Incident VTE cases (n = 653) and a subcohort (n = 1,774) were derived from the Tromsø Study (1994–2012). DNA was genotyped for rs8176719 (ABO), rs6025 (F5), rs1799963 (F2), rs2036914 (F11), and rs2066865 (FGG). Hazard ratios (HRs) for VTE with 95% confidence intervals (CIs) were estimated according to predefined MPV-strata (<8.5, 8.5–9.5, ≥9.5 fL) and number of risk alleles for each individual SNP and the GRS (0–1, 2–3, ≥4 risk alleles) in models adjusted for age, sex, body mass index, and platelet count.Results The combination of high MPV and risk alleles, either as individual SNPs or the GRS, had an additive effect on VTE risk. Compared with subjects with MPV <8.5 fL and 0–1 risk allele, those with high MPV (≥9.5 fL) and ≥4 risk alleles had HRs of 2.80 (95% CI: 1.77-4.43) for overall VTE and 4.60 (95% CI: 2.20–9.60) for unprovoked events, respectively, but there was no supra-additive effect on risk estimates.Conclusion The combination of high MPV and prothrombotic genotypes had an additive effect on VTE risk, suggesting there is no biological interaction between these risk factors in the pathogenesis of VTE.
Keywords: deep vein thrombosis; interaction; mean platelet volume; single nucleotide polymorphism; venous thromboembolism